Firework injuries are increasing in the United States: An analysis of the National Emergency Department Sample - Cindy C. Bitter; Zidong Zhang; Andrew W. Talbert; Alizabeth K. Weber; Leslie Hinyard (Journal of the American College of Emergency Physicians Open)
Abstract Background Firework‐related injuries cause significant morbidity to persons in the United States and globally. Prior studies have shown that hands and eyes are frequently injured, with loss of hand function and blindness being common after serious injury. Many jurisdictions in the United States have relaxed laws governing sales of consumer fireworks in recent years. Given the increased availability of consumer fireworks, we sought to determine the incidence of firework‐related injuries compared with historical controls. Methods Firework‐related injuries were identified in the National Emergency Department Sample (NEDS) using the corresponding International Classification of Disease codes for the years 2008–2017. Demographics, timing of presentation, and hospital characteristics were analyzed. Data were weighted to approximate population estimates of injury. Statistical analyses were completed using SAS. The National Electronic Surveillance System was also queried for firework‐related visits to check for consistency in observed trends. Results There were an estimated 7699 injuries attributed to fireworks in 2017 (2.37 per 100,000 population) compared with 5727 (1.88 per 100,000 population) in 2008. The majority of victims were male (74.6%), and injuries clustered in the pediatric and young adult age groups. The Midwest and South (both 38.1%) had more firework‐related injuries compared with the West (15.6%) and Northeast (8.2%) regions. Most visits occurred in July (71.4%) with smaller peaks in June (6.9%) and January (6.0%). Patients were disproportionately seen in trauma centers (34.0%) and teaching hospitals (49.6%). Conclusion Emergency department visits for firework injuries are increasing in the United States. Pediatric patients and young adult males comprise the majority of victims. Injuries are clustered around the Fourth of July and New Year's holidays. Public health interventions targeted at high‐risk groups may reduce the burden of injury.